2015
DOI: 10.1039/c5cy00798d
|View full text |Cite
|
Sign up to set email alerts
|

Base-regulated tunable synthesis of pyridobenzoxazepinones and pyridobenzoxazines

Abstract: A base-regulated one-pot protocol for the tunable synthesis of pyridobenzoxazepinones and pyridobenzoxazines has been developed. The preparation of pyridobenzoxazepinones is achieved in moderate to good yield by utilizing aromatic nucleophilic substitution(SNAr, O-arylation)/carbonylation tandem reaction. Mechanistic studies suggest that SNAr (Oarylation) proceeds prior to the aminocarbonylation. Through the regulation of bases, pyridobenzoxazines can be obtained via successive SNAr (O-arylation and then N-ary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Although compounds of these types have previously been reported, , the conditions under which they have been prepared are often significantly harsher than those described above (e.g., 10 equiv of activated Cu, 160 °C). , Moreover, many of the reported routes are vulnerable to the Smiles rearrangement, leading to the incorrect (undesired) isomer. For example, we have found that recent reports of the syntheses of substituted 4-azaphenothiazines and 4-azaphenoxazines lead to 1-azaphenothiazines and 1-azaphenoxazines, respectively (see SI for complete details). Not unexpectedly, it is difficult to assign the structures of these molecules simply from their NMR spectra, examples of which are included in Figure (see the SI for 13 C NMR spectra) .…”
mentioning
confidence: 99%
“…Although compounds of these types have previously been reported, , the conditions under which they have been prepared are often significantly harsher than those described above (e.g., 10 equiv of activated Cu, 160 °C). , Moreover, many of the reported routes are vulnerable to the Smiles rearrangement, leading to the incorrect (undesired) isomer. For example, we have found that recent reports of the syntheses of substituted 4-azaphenothiazines and 4-azaphenoxazines lead to 1-azaphenothiazines and 1-azaphenoxazines, respectively (see SI for complete details). Not unexpectedly, it is difficult to assign the structures of these molecules simply from their NMR spectra, examples of which are included in Figure (see the SI for 13 C NMR spectra) .…”
mentioning
confidence: 99%
“…The nature of these transformations has been widely discussed in several reviews where a wide variety of approaches have been described . Recently, the selective and catalytic C–F bond cleavage mediated by transition metal complexes has been reported . However, the use of transition metals implies several drawbacks in industry, due to high costs, purification processes, or metal toxicity which can be found in the final products.…”
Section: Introductionmentioning
confidence: 99%